(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the association between monocyte to HDL-C ratio and renal function in patients with type 2 diabetes mellitus, with particular emphasis on overweight and obese individuals. Subjects and methods: This cross-sectional study included 262 patients diagnosed with type 2 diabetes mellitus who attended the Outpatient Department of University Medical Center Ho Chi Minh City - Campus 2. Patients were stratified according to BMI (< 25 kg/m² and ≥ 25 kg/m²) for subgroup analysis. Results: Among patients with BMI ≥ 25 kg/m², monocyte to HDL-C ratio values were significantly higher and monocyte to HDL-C ratio was negatively correlated with eGFR (r = -0.28, p = 0.0063) and positively correlated with UACR (r = 0.24, p = 0.0208). In this subgroup, multivariable regression analysis demonstrated that monocyte to HDL-C ratio was an independent predictor of eGFR decline after adjustment for age and hemoglobin (p < 0.001) and predicted eGFR < 60 mL/min/1.73 m², with an area under the receiver operating characteristic curve of 0.8084. Conclusions: Monocyte to HDL-C ratio is independently associated with impaired renal function in patients with type 2 diabetes mellitus. These findings suggest that monocyte to HDL-C ratio may serve as a simple and reliable inflammatory - metabolic marker for early identification of chronic kidney disease risk in clinical practice, particularly among overweight and obese patients.